ANALISIS PENGARUH KEHALUSAN ABU TERBANG (ABU SEKAM PADI) TERHADAP FLEKSIBELITAS DAN DURABILITAS AC-WC NR - Farlin Rosyad; Agung Rahmatullah (Rang Teknik Journal, 2024)
Roads are an important and main foundation in moving the wheels of the public and territorial economy, considering their significant and main ability to support the appropriation of labor and products as well as the versatility of the population. Roads enable everyone to get services such as education, health care and employment. Asphalt What was used in this research was SIR 20 rubber asphalt (Standard Indonesian Rubber) which came from PT MBS (Modified Bitumen Sumatra). This research was carried out with the aim of finding out how much influence the fineness of rice husk ash as a fine material substitute has on the AC-WCNR coated asphalt concrete mixture in terms of durability and flexibility. And to find out what the optimum mixture value of rice husk ash is as a substitute for fine material in the AC-WCnr asphalt mixture. The percentage of Au content of rice husk used in research II is 3 variations 4%, 6%, 8%, and to use 4 zones, zone 0, zone 1, zone 2, zone 3 as a substitute for fine material mixed with AC-WC NR and test specimens normal without a mixture of rice husk ash. This research tested using the Marshall test method by reviewing the effect of rice husk ash on flexibility and durability. Based on the Marshall parameter test results in terms of zone variations and the percentage of substitution content for rice husk ash, the flow value can be concluded that the optimum value for using rice husk ash content in zone 2 is 4% variation, namely 3.74mm, and in zone 2, 8% variation has decreased by 3.50 mmm. The durability value of the mixture is seen from variations in the substitution level of rice husk ash, namely that the optimum variation in substitution for rice husk ash occurs in the 4% zone 2 variation, namely 96%.Keywords: Rice Husk Ash, Rubber Asphalt, AC-WC NR, Durability and Flexibility